Classification of brain processing indicators in financial officers - Sittiprapaporn, Phakkharawat; Carmazzi, Arthur F (Asian Journal of Medical Sciences, 2019)
Background: Arthur F. Carmazzi discovered new way of identifying the human brain’s clarity based on the foundations of genetic neurosciences. The specific terminology of “Ambiguity Relief” was used to refer to the human brain’s processing that supports evaluating information to relate new context to existing knowledge, simplifying ideas, making decisions, and problem solving into actionable elements. Aim and Objective: This study identified the relationship between brain processing indicator and communication of financial officers in Thailand by using the Colored Brain Communication Inventory. Materials and Methods: Fifty participants were involved in this study. All participants were assessed by using the Colored Brain Communication Inventory developed by Arthur F. Carmazzi. Results: All participants were thirty-one males (62%) and nineteen females (38%). There were eleven persons worked as Manager, considered 25%. Nine participants worked as Director and seven participants worked as Deputy Director and Senior Manager were about 18%, 14%, and 14%, respectively. Five participants worked as Senior Director were in the amount of 10% of all the participants while two participants worked as Senior Officer and Officer were 4% and 4%, respectively. Of the fifty participants, the highest number of 28 participants (56%) were reported as Green Brain Processing while 12 participants (24%) were reported as Purple Brain Processing. The less of 7 participants (14%) were reported as Red Brain Processing while only 3 participants (6%) were reported as Blue Brain Processing, respectively. Conclusion: This study is the first study to explore the effects of brain processing indicator and communication on the leadership and working environment by using Colored Brain Communication Inventory tool in Thailand. By adopting conceptual and hypotheses of Colored Brain model, any awareness by participants might help their team members adopt a cooperation attitude instead of trying to change others beyond their own processes which creating frustration on both sides.